Asas Proporsionalitas: Perspektif Hukum Positif dan Maqosid Syariah dalam Sistem Peradilan Pidana - Fatoni, Syamsul; Rusdiana, Erma; Rosyadi, Imron; Rozikin, Opik (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The principle of proportionality is based on the principle of balance between the interests of the perpetrator, the victim and the state (on behalf of the society) in relation to the suitability between the crime that has been committed and the sanctions imposed as an important part of the criminal justice system. The purpose of this study is to analyse the existence of the principle of proportionality, from the perspective of positive law and maqasid sharia in the criminal justice system. The type of the present study is a normative juridical research with a statutory approach, a case study approach, and a comparative approach by using primary legal materials, secondary materials, and tertiary legal materials, with qualitative analysis. The results of the study reveal that the existence of the principle of proportionality from the perspective of positive law and maqasid sharia in the criminal justice system is essential, especially in the criminal justice system by considering the objectives of the imposed punishment and the guidelines for imposing such punishment. Therefore, synchronisation of the criminal justice system is needed, namely substantial synchronisation, structural synchronisation and cultural synchronisation to realise the objectives of the fair and just law, in addition to the benefits and certainty for the interests of the perpetrator, the victim, and the state. The principle of proportionality must be well configured in the Positive Law, especially Criminal Law, as contained in the values of Pancasila as the philosophy and way of life of the Indonesian nation, in addition to the ideals of Islamic Law in maqasid sharia which reflects the intent or purpose of law as the philosophy of Muslims for the benefit of the universe ( rahmatan lil 'alamin ) such as hifdz ad-din , hifdz an-nafs , hifdz al-aql , hifdz al-mal and hifdz an-nasl which serve as the symbiotic paradigms.Keywords: criminal justice, maqasid sharia, proportionality, synchronization. AbstrakAsas proporsionalitas yang mendasarkan pada prinsip keseimbangan antara kepentingan pelaku, korban dan negara (masyarakat) berkaitan  adanya kesesuaian antara pidana yang telah dilakukan dengan sanksi yang diterimanya adalah bagian penting dalam sistem peradilan pidana. Tujuan penelitian ini adalah menganalisis eksistensi asas proporsionalitas, perspektif hukum positif dan maqosid syariah dalam sistem peradilan pidana. Jenis penelitiannya adalah yuridis normatif dengan statute approarch, case approarch, comparative approarch dan menggunakan bahan hukum primer, bahan sekunder, bahan hukum tertier, serta analisis kualitatif. Hasil studi mengungkapkan bahwa eksistensi asas proporsionalitas, perspektif hukum positif dan maqosid syariah dalam sistem peradilan pidana sangat penting, khususnya dalam sistem pemidanaan dengan memperhatikan tujuan pemidanaan dan pedoman pemidanaan. Oleh sebab itu, diperlukan sinkronisasi sistem peradilan pidana yaitu sinkronisasi substansial, sinkronisasi struktural dan sinkronisasi kultural untuk mewujudkan tujuan hukum yang berkeadilan di samping kemanfaatan dan kepastian bagi kepentingan pelaku, korban, dan negara (masyarakat). Asas proporsionalitas tersebut harus terkonfigurasikan dengan baik dalam hukum positif terutama Hukum Pidana yang terkandung dalam nilai-nilai Pancasila sebagai falsafah dan way of life bangsa Indonesia, di samping cita Hukum Islam dalam maqasid al syariah yang memuat maksud atau tujuan hukum sebagai falsafah Umat Islam demi kemaslahatan bagi alam semesta (rahmatan lil ‘alamin) seperti hifdz ad-din, hifdz an-nafs, hifdz al-aql, hifdz al-mal dan hifdz an-nasl yang merupakan paradigma simbiotik.Kata Kunci: Asas Proporsionalitas, Maqasid Sharia, Sinkronisasi, Sistem Peradilan Pidana.